Is Vestibular Neuritis an Immune Related Vestibular Neuropathy Inducing Vertigo?. (16th January 2014) - Greco, A.; Macri, G. F.; Gallo, A.; Fusconi, M.; De Virgilio, A.; Pagliuca, G.; Marinelli, C.; de Vincentiis, M.
Abstract : Objectives . To review the current knowledge of the aetiology of vestibular neuritis including viral infections, vascular occlusion, and immunomediated mechanisms and to discuss the pathogenesis with relevance to pharmacotherapy. Systematic Review Methodology . Relevant publications on the aetiology and treatment of vestibular neuritis from 1909 to 2013 were analysed. Results and Conclusions . Vestibular neuritis is the second most common cause of peripheral vestibular vertigo and is due to a sudden unilateral loss of vestibular function. Vestibular neuronitis is a disorder thought to represent the vestibular-nerve equivalent of sudden sensorineural hearing loss. Histopathological studies of patients who died from unrelated clinical problems have demonstrated degeneration of the superior vestibular nerve. The characteristic signs and symptoms include sudden and prolonged vertigo, the absence of auditory symptoms, and the absence of other neurological symptoms. The aetiology and pathogenesis of the condition remain unknown. Proposed theories of causation include viral infections, vascular occlusion, and immunomediated mechanisms. The management of vestibular neuritis involves symptomatic treatment with antivertiginous drugs, causal treatment with corticosteroids, and physical therapy. Antiviral agents did not improve the outcomes.